Melasma management: Unveiling recent breakthroughs through literature analysis - Darshan Kumar R; Richa Sood; Prashant Tiwari (Health Sciences Review)
Melasma is a prevalent acquired hyperpigmentation disorder characterized by irregular brownish patches on areas of the skin frequently exposed to sunlight. Although benign, it can significantly affect an individual's quality of life due to limited treatment options. Over the years, various therapeutic approaches, including topical agents, chemical peels, laser treatments, and oral medications, have been explored. However, managing melasma remains challenging, with high recurrence rates and inconsistent therapeutic outcomes. This review focuses on recent methodological advancements in elucidating the pathophysiology of melasma and the development of novel treatment strategies. Research leveraging histological analyses, genetic profiling, and biochemical assays has elucidated novel therapeutic targets, including oxidative stress pathways and inflammatory mediators. Advances in topical formulations, such as combination therapies containing tyrosinase inhibitors, antioxidants, and anti-inflammatory agents, have shown promising results in improving pigmentation and preventing recurrence. Furthermore, targeted delivery systems, such as nanoparticles and liposomes, have enhanced the efficacy and penetration of active ingredients, leading to better clinical outcomes.In addition to topical treatments, recent studies have highlighted the efficacy of emerging modalities such as fractional lasers, intense pulsed light (IPL), and microneedling in the management of melasma. These techniques offer precise targeting of melanin without causing significant epidermal damage, thus minimizing the risk of post-inflammatory hyperpigmentation. Moreover, advances in oral medications have shown encouraging results in reducing melanin production and preventing melasma recurrence.In conclusion, current advances in melasma management provide great opportunities for improving outcomes and increasing patient satisfaction. A multidisciplinary approach integrating dermatologists, cosmetic surgeons, and skincare professionals is essential for designing comprehensive and individualized treatment regimens. These advancements underscore the potential for improving patient outcomes and satisfaction while emphasizing the need for robust research to optimize therapeutic strategies.